Studies on the effects of various parameters on the performance of 'Petti and Para' - SAJI M. KURIAKOSE; Dr. K John Thomas (Guide) (Tavanur 1994 Kelappaji College of Agricultural Engineering and Technology)
Studies on the effects of various parameters on the performance of 'Petti and Para'
Studies on the effects of various parameters on the performance of 'Petti and Para'